1981
DOI: 10.1121/1.386929
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in identifying and discriminating CV syllables

Abstract: The purpose of this experiment was to determine whether age-related differences would be observed for identification and discrimination of synthesized, five-formant CV syllables among listeners who showed equal performance scores on a standard clinical test of speech understanding. A second question concerned the relations between performance on identification and discrimination tasks as a function of age. Two 13-item continua that varied in the place of articulation feature ([ba, da, ga]) were used; they diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 0 publications
3
30
1
Order By: Relevance
“…Cse Âpe et al (1997) observed no changes of phonetic sensitivity (measured by the MMN) to place of articulation contrasts between the age of six and ten, but a large variability of the MMN to voicing contrasts in younger children (6±7 years). In a study by Elliott et al (1981) 10 year old children performed signi®-cantly better on a labeling task with natural speech sounds contrasting in place of articulation than 6 year olds. So, further research is needed to clarify the maturation of phonetic sensitivity measured by behavioral tasks on the one hand and ERP-measures like the MMN on the other hand.…”
Section: Erp Measuresmentioning
confidence: 97%
“…Cse Âpe et al (1997) observed no changes of phonetic sensitivity (measured by the MMN) to place of articulation contrasts between the age of six and ten, but a large variability of the MMN to voicing contrasts in younger children (6±7 years). In a study by Elliott et al (1981) 10 year old children performed signi®-cantly better on a labeling task with natural speech sounds contrasting in place of articulation than 6 year olds. So, further research is needed to clarify the maturation of phonetic sensitivity measured by behavioral tasks on the one hand and ERP-measures like the MMN on the other hand.…”
Section: Erp Measuresmentioning
confidence: 97%
“…For example, there has been extensive study of perception of the voiced consonants associated with /ba/-/da/-/ga/,l which are differentiated perceptually, in large part, because the listener discriminates frequencytransitions,or changes in "formants. " Both young children (Elliott et al, 1981) and older adults (Elliott, Busse, & Ballet, 1985) exhibit poorer discrimination of these CVs than do young adults. Because discrimination of these CVs involves discrimination of different rates of frequency change, we were interested in examining the ability of listeners of widely different ages to discriminate frequency changes that simulate the second formants of speech.…”
mentioning
confidence: 99%
“…Requests for reprints shouldbe sent to Lois Elliott, Program in Audiologyand Hearing Impairment, Northwestern University, 2299 Sheridan Road, Evanston, IL 60208. 181 1980) or to discriminate computer-synthesized speech sounds (Elliott, 1986;Elliott, Busse, Partridge, Rupert, & DeGraaff, 1986;Elliott, Longinotti, Meyer, Raz, & Zucker, 1981). Abundant evidence has also demonstrated that listeners over 60-65 years of age usually do not understand speech as well as do younger adults (Working Group on Speech Understanding and Aging, 1988).…”
mentioning
confidence: 99%
“…When Elliott, Longinotti, Meyer, Raz, and Zucker (1981) measured the smallest between-syllable difference that could be discriminated (here termed, "just noticeable differences," or JNDs), they found that normalhearing 6-year-old children had larger JNDs than normal to-year-olds or normal adults. In other work, which used only the three exemplars [bo], [do], and [go], Elliott, Longinotti, Clifton, and Meyer (1981) found that 6-year-old children required higher intensities to identify these syllables and also exhibited more shallow slopes for their performance-intensity functions than did 10-year-oIds.…”
mentioning
confidence: 99%